2016
DOI: 10.1371/journal.pone.0146452
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Constant Thickness Cartilage Models vs. Patient Specific Cartilage Models for an Optimized Computer-Assisted Planning of Periacetabular Osteotomy

Abstract: Modern computerized planning tools for periacetabular osteotomy (PAO) use either morphology-based or biomechanics-based methods. The latter relies on estimation of peak contact pressures and contact areas using either patient specific or constant thickness cartilage models. We performed a finite element analysis investigating the optimal reorientation of the acetabulum in PAO surgery based on simulated joint contact pressures and contact areas using patient specific cartilage model. Furthermore we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…Patient-specific CT data for both normal and dysplastic hips were employed in several studies 42,43,45 . Others had only access to either normal 17 or dysplastic 15,47,48 patient-specific CT data and generated models of dysplastic or close-to-normal hips by deforming the acetabular rim or changing morphological parameters of the acetabulum through virtual osteotomy. One study employed patient-specific CT data of dysplastic hips pre-and post-osteotomy 16 .…”
Section: Geometrymentioning
confidence: 99%
See 3 more Smart Citations
“…Patient-specific CT data for both normal and dysplastic hips were employed in several studies 42,43,45 . Others had only access to either normal 17 or dysplastic 15,47,48 patient-specific CT data and generated models of dysplastic or close-to-normal hips by deforming the acetabular rim or changing morphological parameters of the acetabulum through virtual osteotomy. One study employed patient-specific CT data of dysplastic hips pre-and post-osteotomy 16 .…”
Section: Geometrymentioning
confidence: 99%
“…CT-based models demonstrate bony anatomy well, but generating accurate geometries of soft tissues (cartilage and ligaments) is difficult since these structures are poorly seen on CT images. Some studies 42,43,45,48 used CT arthrography (CTA), which is invasive but clearly demonstrates articular cartilage (AC) boundaries, to directly model cartilage thickness (0.5e2.8 mm 45 , 0.8e2.0 mm 42,43 ). Non- x Includes only the acetabular cup.…”
Section: Geometrymentioning
confidence: 99%
See 2 more Smart Citations
“…FEA has been used very similarly to DEA to evaluate joint contact stresses in normal versus dysplastic hips [81][82][83][84] and to evaluate or guide surgical interventions based on reduction in contact stress. [85][86][87][88][89][90] Modeling overcorrection and residual impingement after PAO can best be performed using FEA, 86 which allows for incorporation of the mechanically complex soft tissues 91 that are at highest risk of developing high stresses and strains and ultimately progressing to failure. 81 A recent FEA modeling study of a small number of acetabular retroversion patients found that while PAO served to offload forces passing through the labrum during several activities of daily living and shift contact stress medially and posteriorly within the articular surface of the acetabulum, peak contact stress in these patients actually increased postoperatively.…”
Section: Computational Analysis Of Joint Mechanics In Dysplasia and Amentioning
confidence: 99%